2021
DOI: 10.1186/s12889-021-10409-4
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and depression among women in rural Pakistan

Abstract: Background Adverse Childhood Experiences (ACEs) are a common pathway to adult depression. This pathway is particularly important during the perinatal period when women are at an elevated risk for depression. However, this relationship has not been explored in South Asia. This study estimates the association between ACEs and women’s (N = 889) depression at 36 months postpartum in rural Pakistan. Method Data come from the Bachpan Cohort study. To cap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
(34 reference statements)
1
23
1
Order By: Relevance
“… 23 In our team’s prior work with a cohort of women in Pakistan at 36 months post partum, we have found that exposure to community violence was much more strongly correlated with maternal depression than other domains such as neglect. 24 A significant potential driver of different findings is the diversity of social, economic and cultural contexts in which the ACEs take place. Hence, studies from multiple geographic regions and population groups make important contributions towards better understanding of how various ACEs may differentially impact mental health.…”
Section: Objectivesmentioning
confidence: 99%
“… 23 In our team’s prior work with a cohort of women in Pakistan at 36 months post partum, we have found that exposure to community violence was much more strongly correlated with maternal depression than other domains such as neglect. 24 A significant potential driver of different findings is the diversity of social, economic and cultural contexts in which the ACEs take place. Hence, studies from multiple geographic regions and population groups make important contributions towards better understanding of how various ACEs may differentially impact mental health.…”
Section: Objectivesmentioning
confidence: 99%
“…Depression is influenced by environmental factors related to social issues, such as childhood experiences, social interactions, and lifestyles. Adverse childhood experiences are risk factors for depression and anxiety in adolescence (37) and are a common pathway to depression in adults (38). Poor interpersonal relationships with classmates, family, teachers, and friends increase the prevalence of depression in adolescents (39).…”
Section: Etiologymentioning
confidence: 99%
“…The prevalence of ACEs, both prospectively and retrospectively, is considerably higher than global and meta-analytic estimates [7]. However, ACEs evidence in low-income, high-violence settings with widespread adversity across the life course is slowly emerging [19,[87][88][89] and highlighting important similarities and differences in the field. Bt30 is one of few cohorts in an LMIC that has reached young adulthood-the period in which human capital disparities are likely to emerge [90].…”
Section: Strengths and Limitationsmentioning
confidence: 97%